Can Talk Reveal Nondeclarative Culture? Deliberation Strategies in Talking About Social Controversies. Issue 4 (21st September 2022) - Delp, Christine; Edgell, Penny
Abstract : Scholars have long debated the kind of cultural information that can be obtained through discursive methodologies. Is it possible to discern implicit, nondeclarative cultural information about research participants from "talk" alone? Using focus group data from the Talking about Social Controversies project, we argue that it is possible to discover limited kinds of nondeclarative culture from talk in sites of situated interaction. We propose the concept of deliberation strategies to describe the different ways people align their personal declarative culture (e.g., beliefs and values) with available forms of public culture (e.g., discourses or institutionally packaged cultural forms). We argue that deliberation strategies are styles of combining personal and public culture, and that they reveal information about (1) the coherence of people's personal declarative culture, (2) people's implicit preferences for alignment between their personal beliefs and policies they would prefer to see adopted for the public at large, and (3) their preferences for coherence at the level of public culture. We show how focusing on deliberation strategies sheds light on the willingness of individuals to accept institutionally packaged "one‐size‐fits‐all" solutions to contemporary social problems.